EVALUASI PENERAPAN PROGRAM KAWASAN TANPA ROKOK DI FAKULTAS HUKUM UNIVERSITAS RIAU - Mohd. Suhaimi; Febriana Sabrian; Darwin Karim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
The implementation of Smoke-free Area program is a protective measure for the community against the risks of health threatsbecause the environment is polluted with cigarette smoke. The implementation of Smoke-free Area program needs to beimplemented in health care facilities, teaching and learning places, playgrounds, worship places, public transportation,workplaces, public places and other places established to protect community from cigarette smoke. The purpose of this studywas to evaluate the implementation of Smoke-free Area program policiy at the Faculty of Law Universitas Riau. This studywas evaluation study. The sample in this study were 140 respondents consists of 95 students, 21 lecturers, and 24 staffs. Theanalysis used was univariate analysis. The results showed that at the input indicator, there was already written policy aboutSmoke-free Area, there was already health education about Smoke-free Area, there was already designated area for smoking,but no staff has been assigned to monitor Smoke-free Area. At the process indicator, socialization of Smoke-free Area policyface-to-face and through print or electronic media has not been maximized, the Smoke-free Area policy announcement alreadyposted through the sign of smoking ban, circular letter and Smoke-free Area sign, but there has been no regulation of tasksand responsibilities of Smoke-free Area implementation, not yet posted Smoke-free Area policy announcements throughposters, wall magazines, and loudspeakers, and there was no counseling about Smoke-free Area and the dangers of smoking& smoking ethics. At the output indicator was found that there were smokers in the Smoke-free Area environment, found nonsmokingstudents/ lecturers/ staffs admonished smoking students/ lecturers/ staffs, found smokers who smoked outside theSmoke-free Area environment, but there was no sanction for those who violate Smoke-free Area. Based on the results, it isrecommended that the Faculty of Law Universitas Riau necessary to maximized the improne health promation regardingSmoke-free Area, provide standardized smoking room, and implement punishment for any Veolator.Keywords: Evaluation, Implementation, Smoke-free Area program